Design and Implementation of Multichannel Data Acquisition and Processing System Using LabVIEW - Dhruva R. Rinku; Gundu Srinath (Institute of Advanced Engineering and Science, 2015)
The data acquisition and processing architecture covers the most demanding applications of continuousmonitoring in industrial field. The multichannel data acquisition is essential for acquiring and monitoring the various signals from industrial sensors. The problem is that the data storage and hardware size, so the multichannel data obtained is processed at runtime and stored in an external storage for future reference. The method of implementing the proposed design is by using the ARM Cortex M-3 Processor to reduce the hardware size. The Cortex M-3 attains high resolution. A Eight channel data acquisition processing (DAQP) and Controlling was designed, developed using the Lab VIEW graphical programming. The module was designed in order to provide high accuracy, storage and portability. The system designed is not specific for any sensor acquisition, so any sensor having signal conditioning circuit built can be connected to the DAQ (Data Acquisition System). ARM controller is used as heart of the DAQ.